Students' critical thinking skills in the learning strategy course - Nurfaizah Nurfaizah; Khamim Zarkasih Putro; Dhiarti Tejaningrum (Jurnal Penelitian Ilmu Pendidikan, 2022)
Critical thinking is a process that aims to make all decisions based on reasonable facts. Critical thinking requires skills in listening and reading which are studied very carefully, can search for and sort out hidden assumptions and explore the consequences of a statement. The purpose of this study is to understand in-depth and describe the implementation of learning in the course of learning strategies to train students to think critically. The subjects of this research are lecturers and students. This research uses a case study qualitative research method. In analyzing the data using the three components of the Miles and Huberman model, namely: data reduction, data presentation, and conclusion. The results of this study indicate that students can think critically in the course of learning strategies and meet several criteria for critical thinking skills, namely students can give simple explanations, students can build basic skills, can conclude, which consists of deductive activities, can provide further explanations on a topic. Problems and students can determine actions and interact with others.